TTC21B contributes both causal and modifying alleles across the ciliopathy spectrum - Davis, Erica E.; Zhang, Qi; Liu, Qin; Diplas, Bill H.; Davey, Lisa M.; Hartley, Jane; Stoetzel, Corinne; Szymanska, Katarzyna; Ramaswami, Gokul; Logan, Clare V.; Muzny, Donna M.; Young, Alice C.; et al. (Nature genetics, 2011)
Nicholas Katsanis and colleagues show that biallelic mutations in TTC21B, encoding the retrograde intraflagellar transport protein IFT139, are associated with diverse ciliopathy phenotypes in humans. They further show that pathogenic alleles of TTC21B are present in as many as 5% of ciliopathy cases, supporting an oligogenic model of disease.